Remote eavesdropping at 200 meters distance based on laser feedback interferometry with single-photon sensitivity. (June 2021) - Xu, Zhong; Li, Jiyang; Zhang, Shulian; Tan, Yidong; Zhang, Xiliang; Lin, Xuling; Wan, Xinjun; Zhuang, Songlin
Highlights: Eavesdropping clear speech within 100 meters and recognizable one within 200 meters Less than 0.91 photon sensitivity per feedback cycle Support a range of incidence angle in ± 60° in the distance of 100 meters Support a range of incidence angle in ±30° in the distance of 200 meters Meet various requirements of acoustic signals detection Abstract: A remote eavesdropping system based on the laser feedback interferometry is proposed. The diffuse objects neighboring the speaker can work as inconspicuous sensors. The modulated incident beam is scattered back to the laser cavity by the objects, forming the self-mixing interference. The huge amplification caused by the self-mixing interference provides the system with ultra-high sensitivity, even the feedback light whose intensity is -104dB lower than the laser output can still be sensed. The comprehensible voice reconstruction of the object at the distance of 200 m can be realized, although only 0.91 photon in each interference modulation cycle is scattered back into the laser cavity. Additionally, the range of the incident angle of the beam can be up to ±45 deg, and the optimal one is ±30 deg. This system can meet various requirements of acoustic signals detection and be potentially applied in fields as disaster relief and remote surveillance.